2017
DOI: 10.1094/pdis-01-17-0117-re
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Real-Time PCR Assay for Direct Identification and Quantification of Pratylenchus penetrans in Soil

Abstract: The root-lesion nematode Pratylenchus penetrans is a major pathogen of potato worldwide. Yield losses may be exacerbated by interaction with the fungus Verticillium dahliae in the potato early dying disease complex. Accurate identification and quantification of P. penetrans prior to planting are essential for developing effective integrated pest control measures. However, distinction between P. penetrans and other Pratylenchus spp. based on morphology is a tedious task. A SYBR Green I-based qPCR assay was deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Similar results were obtained for the detection and quantification of P. thornei (Mokrini et al, 2014). In both studies, there were no cases of underestimation or overestimation compared to enumeration under the microscope, as previously reported by other qPCR methods (Sato et al, 2007(Sato et al, , 2010Goto et al, 2011;Baidoo et al, 2017;Oliveira et al, 2017;Dauphinais et al, 2018). Nevertheless, further tests must be done to check their reproducibility in other laboratories worldwide.…”
Section: Molecular Diagnostics Of Rootlesion Nematodessupporting
confidence: 87%
See 3 more Smart Citations
“…Similar results were obtained for the detection and quantification of P. thornei (Mokrini et al, 2014). In both studies, there were no cases of underestimation or overestimation compared to enumeration under the microscope, as previously reported by other qPCR methods (Sato et al, 2007(Sato et al, , 2010Goto et al, 2011;Baidoo et al, 2017;Oliveira et al, 2017;Dauphinais et al, 2018). Nevertheless, further tests must be done to check their reproducibility in other laboratories worldwide.…”
Section: Molecular Diagnostics Of Rootlesion Nematodessupporting
confidence: 87%
“…However, these methods showed an overestimation of nematode numbers compared to conventional enumeration under the microscope (Baidoo et al, 2017;Dauphinais et al, 2018).…”
Section: Molecular Diagnostics Of Rootlesion Nematodesmentioning
confidence: 91%
See 2 more Smart Citations
“…Since then, numerous studies have identified and differentiated Pratylenchus spp. to the species level using DNA-based molecular diagnostic methods such as PCR restriction fragment length polymorphism (RFLP), species-specific PCR, and DNA sequencing [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The RFLP potion of the RFLP–PCR is an additional time-consuming step that is not amenable to commercial high-throughput applications [ 22 ].…”
Section: Introductionmentioning
confidence: 99%